Error Analysis of Word Order in Mandarin Sentences by Beginner Learners: A Case Study of First-Year Students at The State University of Makassar - Asmuliyati Nahnu; Ria Riski Marsuki (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2026)
This study aims to analyze the types and frequency of word order errors in Mandarin sentences made by beginner learners. The data were obtained from written tests completed by 17 first-year students of the Mandarin Language Education Study Program at the State University of Makassar. The test consisted of 10 questions in two formats: (1) arranging scrambled words into grammatically correct sentences, and (2) translating Indonesian sentences into Mandarin. The results indicate that word order errors primarily occurred in five aspects, namely: (1) the placement of temporal adverbs, frequency adverbs, and interrogative words; (2) the position of resultative/aspectual complements; (3) the order of serial verbs; (4) the use of degree adverbs; and (5) the structure of numerals with classifiers. These errors were attributed to interference from the more flexible word order of the Indonesian language, as well as the students' insufficient understanding of Mandarin syntactic rules. These findings highlight the need for a systematic emphasis on learning sentence structures. The implications of this research are expected to serve as a foundation for formulating more effective teaching strategies for Mandarin sentence patterns for beginner learners.